XIX a. Lietuvos knyga kaip Lietuvos knygos muziejaus ekspozicijos objektas - Navickienė, Aušra (Knygotyra, 2003)
Speak in professional terms, a museum about Lithuanian book, which is undergoing the period of establishment, is a kind of a book museum, a new kind of the museum at all, and can be called Lithuanian book museum. Its main objective should be to collect, store, preserve, research and exhibit such a complex and multiform phenomenon as Lithuanian book, revealing its main features from the historical as well as from the modern point of view. The exposition should reflect the overall cycle of book existence in the society, that part of Lithuanian cultural and material life, which should witness the appearance of the book, its development and existence dating back to the first facts of documentary communication until the present day. What is Lithuanian book, what is the 19th century Lithuanian book, what should the exposition contents of this particular historical period in Lithuania be? Lithuanian book embraces all the printed matter in all the languages (not only in Lithuanian) published in the territory of Lithuania, including manuscripts as well, especially for the analysis of the very early stages of book development. Thus, matter, published in Lithuania and beyond its borders, to satisfy the needs of Lithuanian inhabitants with heterogeneous cultural background and language and different religious beliefs. The 19th century Lithuanian book is a complicated subject both for researchers of book history and founders of book museums as well. Historiography of book research has an agreed structural division of Lithuanian book identifying books in Lithuanian and foreign language, Minor Lithuania’s and Great Lithuania’s and emigrants’ books. This division seems to be suitable for the exposition in a book museum. Having existed in different conditions and having their own peculiarities the books of emigrants and those of Minor and Great Lithuania could be exhibited separately on their own, presenting the history of book in a chronological order. Creating the 19th century Great Lithuania book exposition, special attention should be made to the periods of book development and its peculiarities. The bottom line of the 19th century book history is the year of 1795, when Lithuania was integrated into Russian Empire after the third division of Polish-Lithuanian State and the country experienced the occupation period of over a hundred years. The development of the book as well as the overall life in the state was under the influence of dynamic and complicated political, economic and cultural changes. The policy of tolerance towards political and cultural identity on the newly annexed territory was changed into the policy „of destruction and annihilation of the origins“, which used to differentiate the territory from Russia, or „reestablishment“ of them. The consequence of this were the crucial changes in control and surveillance measures of the printed matter, the restriction on the usage of the Polish and Lithuanian languages and the introduction of the Russian language into the public life of the country. At the same time Lithuanian as well as other European countries were experiencing the period of rebirth and revival. The beginning of ethno-cultural movement modified the approach towards national languages and the publication of books in those languages. The top part of 19th century book development is the year of 1904. That time saw the abolishment of the ban on printed matter in Latin script, the latter fact having had the fatal influence on the existence of the book in the second part of the 19th century. The 40-year ban on printed matter sets itself apart in the development of the book and should comprise a separate part in the exposition of the 19th century book of Great Lithuania.